Fufang Xueshuantong Improves Diabetic Cardiomyopathy by Regulating the Wnt/β-Catenin Pathway. (19th September 2022) - Peng, Meizhong; Liu, Hanying; Ji, Qingxuan; Ma, Pan; Niu, Yiting; Ning, Shangqiu; Sun, Huihui; Pang, Xinxin; Yang, Yuqian; Zhang, Yuting; Han, Jing; Hao, Gaimei
Abstract : Diabetic cardiomyopathy (DCM) is one of the main complications of diabetic patients and the major reason for the high prevalence of heart failure in diabetic patients. Fufang Xueshuantong (FXST) is a traditional Chinese medicine formula commonly used in the treatment of diabetic retinopathy and stable angina pectoris. However, the role of FXST in DCM has not yet been clarified. This study was conducted to investigate the effects of FXST on diabetic myocardial lesions and reveal its molecular mechanism. The rats were intraperitoneally injected with 65 mg/kg streptozotocin (STZ) to induce diabetes mellitus (DM). DM rats were given saline or FXST. The rats in the control group were intraperitoneally injected with an equal amount of sodium citrate buffer and gavaged with saline. After 12 weeks, echocardiography, heart weight index (HWI), and myocardial pathological changes were determined. The expression of transforming growth factor-beta1 (TGF- β 1), collagen I, and collagen III was examined using immunofluorescence staining and western blot. The expressions of Wnt/ β -catenin signaling pathway-related proteins and mRNA were detected by western blot and real-time PCR. The results showed that FXST significantly improved cardiac function, ameliorated histopathological changes, and decreased HWI in the DM rats. FXST significantly inhibited the expression of myocardial TGF- β 1, collagen I, and collagen III in DM rats. Furthermore, FXST significantly inhibited the Wnt/ β -catenin pathway. Taken together, FXST has a protective effect on DCM, which might be mediated by suppressing the Wnt/ β -catenin pathway.